Carvacrol enhances the sensitıvity of cetuximab in lung cancer cells through inducing apoptosis and cell cycle arrest (Bangladesh Journal of Pharmacology, 2025)
The intention of this work was to analyze that carvacrol could enhance cancer-inhibiting potency of cetuximab (monoclonal antibody) in lung cancer cells. The combination of cetuximab and carvacrol was found to co-operatively suppress cell proliferation by enhancing apoptosis and inducing cell cycle arrest in A-549 and H1299 cells. Furthermore, the combination therapy triggered cell death by inducing membrane disruption. The most effective combinations were IC₁₀ cetuximab + IC₁₀ carvacrol for A-549 and IC₂₀ cetuxi-mab + IC₁₀ carvacrol for H1299 (CI = 2.0). LDH activity increased by 101% in A-549 and 239% in H1299 (p